2022
DOI: 10.1063/5.0123925
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis for suppression of charge growth using nested grooves in rectangular waveguides

Abstract: Multipactor mitigation is of relevance to microwave applications, and external magnetic fields, surface modifications, and materials engineering have previously been utilized for this purpose. In this contribution, geometric modifications made to rectangular waveguide surfaces in the form of nested grooves are investigated for the suppression of multipactor growth. A time-dependent kinetic scheme is used to simulate electron dynamics that folds in electron trapping at the nested groove structures, with inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Conversely, particle traps constructed in the center or near the anode exert less influence on the electric field at the CTJ, and because of the groove's hindering effect on the development of SEAs, particle traps positioned at these locations will enhance the flashover voltage of the dielectric. 28 According to the optimization results mentioned above, the most significant improvement in flashover voltage can be achieved by utilizing a single-groove particle trap positioned in the center between the electrodes. Building upon this finding, the structural parameters of the particle trap are further optimized as follows.…”
Section: B Parameter Optimization Of the Particle Trapmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, particle traps constructed in the center or near the anode exert less influence on the electric field at the CTJ, and because of the groove's hindering effect on the development of SEAs, particle traps positioned at these locations will enhance the flashover voltage of the dielectric. 28 According to the optimization results mentioned above, the most significant improvement in flashover voltage can be achieved by utilizing a single-groove particle trap positioned in the center between the electrodes. Building upon this finding, the structural parameters of the particle trap are further optimized as follows.…”
Section: B Parameter Optimization Of the Particle Trapmentioning
confidence: 99%
“…Consequently, SEA develops more readily at the bottom than at the sidewall. 28 In summary, for particle traps with relatively wide widths, there exists a critical depth that can restrict the SAC to a lower level, thereby increasing the flashover voltage. As illustrated in Fig.…”
Section: B Parameter Optimization Of the Particle Trapmentioning
confidence: 99%
“…These methods have achieved success for the metals and inorganic ceramic dielectrics [29]. For metals, the effectiveness of groove structures in reducing SEY has been highlighted in recent literature [30][31][32][33]. In 2020, Ludwick et al reported a study on SEY modulation on microporous gold surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In a high degree of vacuum without an ionization source for discharge initiation, flashover begins from the cathode triple junction (CTJ) where electrode, insulator, and vacuum adjoin [14]. Due to the transient and nonequilibrium nature of the flashover process, numerical modeling provides valuable supplements to the experimental observations [15][16][17][18][19][20][21][22]. The particle-in-cell (PIC) method is a widely adopted numerical approach that is implemented in most, if not all, recent vacuum flashover simulation studies.…”
Section: Introductionmentioning
confidence: 99%